Vasoactive Intestinal Peptide Deficiency Is Associated With Altered Gut Microbiota Communities in Male and Female C57BL/6 Mice - Bains, Manpreet; Laney, Caleb; Wolfe, Annie E.; Orr, Megan; Waschek, James A.; Ericsson, Aaron C.; Dorsam, Glenn P. (Frontiers in Microbiology, 2019)
Vasoactive intestinal peptide (VIP) is crucial for gastrointestinal tract (GIT) health. VIP sustains GIT homeostasis through maintenance of the intestinal epithelial barrier and acts as a potent anti-inflammatory mediator that contributes to gut bacterial tolerance. Based on these biological functions by VIP, we hypothesized that its deficiency would alter gut microbial ecology. To this end, fecal samples from male and female VIP+/+, VIP+/- and VIP-/- littermates (n=47) were collected and 16S rRNA sequencing was conducted. Our data revealed significant changes in bacterial composition, biodiversity and weight loss from VIP-/- mice compared to VIP+/+ and VIP+/- littermates, irrespective of sex. The gut bacteria compositional changes observed in VIP-/- mice was consistent with gut microbial structure changes reported for certain inflammatory and autoimmune disorders. Moreover, predicted functional changes by PICRUSt software suggested an energy surplus within the altered microbiota from VIP-/- mice. These data support that VIP plays an important role in maintaining microbiota balance, biodiversity and GIT function, and its genetic removal results in significant gut microbiota restructuring and weight loss.